2021
DOI: 10.3389/fcvm.2021.691646
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Human Immune Responses to GAS Antigens as a Diagnostic Indicator for ARF: A Systematic Review

Abstract: Background: Previous studies have established that streptococcal antibody titer is correlated with a diagnosis of acute rheumatic fever (ARF). However, results vary in the usefulness of GAS antibodies, particularly anti-streptolysin-O (ASO) and anti-DNase B, in confirming a recent GAS infection. Therefore, we sought to provide, from published studies, an evidence-based synthesis of the correlation of streptococcal serology to establish the usefulness of immunological data in aiding the diagnosis of ARF. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
(65 reference statements)
1
1
0
Order By: Relevance
“…In the current study, 60% of the participants in groups 1 and 3 demonstrated antibody increases against either SLO or DNaseB, which is similar to the 67% observed in the previous study. While there is not a standardized ELISA for new immune responses to SLO and DNaseB, these results confirm previous observations showing the relatively low sensitivity of these antibody responses in detecting prior Strep A infection ( 8 , 15 , 23 ). This study also highlights the usefulness of employing a change in the antibody response from one time point to the next for accurately describing a positive association with a particular antigen.…”
Section: Discussionsupporting
confidence: 87%
“…In the current study, 60% of the participants in groups 1 and 3 demonstrated antibody increases against either SLO or DNaseB, which is similar to the 67% observed in the previous study. While there is not a standardized ELISA for new immune responses to SLO and DNaseB, these results confirm previous observations showing the relatively low sensitivity of these antibody responses in detecting prior Strep A infection ( 8 , 15 , 23 ). This study also highlights the usefulness of employing a change in the antibody response from one time point to the next for accurately describing a positive association with a particular antigen.…”
Section: Discussionsupporting
confidence: 87%
“…Nearly a century after AHA began and half a century after commissioning of Cardiovascular Disease in the Young, the Children's Strategically Focused Research Network (SFRN) was established to apply state‐of‐the‐art basic, clinical, and population science strategies and train the next generation of pediatric cardiology scientists while still embodying Cardiovascular Disease in the Young's original focus on RHD, CHD, and preventive cardiology. The Children's SFRN directly and proudly builds on work done by the early pioneers in of pediatric cardiovascular science within AHA in the 1940s and 1950s.This article highlights the hypotheses, goals, accomplishments, challenges, and future directions of each center; provides an overview of collaboration efforts (Table 1 ) 1 , 2 , 3 , 4 and trainee accomplishments (Table 2 ) 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ; and summarizes how we can leverage the output of this SFRN to advance pediatric cardiovascular science.…”
mentioning
confidence: 99%